Peran Komunikasi yang Efektif dalam Membangun Hubungan Suami-Istri Guna Meningkatkan Pertumbuhan Spiritual - Edison Edison; Yanto Paulus Hermanto (Sekolah Tinggi Teologi Jaffray Jakarta, 2023)
Communication is an important thing in a husband and wife relationship. Good communication will also increase the spiritual level of each family member. Therefore the author will examine how effective communication can build a husband and wife relationship that grows spiritually. The research method to answer the formulation of this problem uses a method with a qualitative approach. The results of the discussion show that married couples must understand the communication barriers and understand how to communicate effectively, to increase the spirituality of each partner.